The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1365-2249.2010.04218.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 2 is a novel autoantigen for anti-endothelial cell antibodies in systemic vasculitis

Abstract: SummaryAnti-endothelial cell antibodies (AECA) have been frequently detected in systemic vasculitis, which affects blood vessels of various sizes. To understand the pathogenic roles of AECA in systemic vasculitis, we attempted to identify target antigens for AECA comprehensively by a proteomic approach. Proteins extracted from human umbilical vein endothelial cells (HUVEC) were separated by two-dimensional electrophoresis, and Western blotting was subsequently conducted using sera from patients with systemic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…In addition to its role in diseases associated with increased ROS, autoantibodies against Prxs have been associated with autoimmune diseases such as Kawasaki disease, systemic sclerosis, and systemic vasculitis (84,125,139). In these studies, sera from patients with and without autoimmune diseases were screened for autoantibodies against different isoforms of Prx.…”
Section: Thioredoxin Target Proteinsmentioning
confidence: 99%
“…In addition to its role in diseases associated with increased ROS, autoantibodies against Prxs have been associated with autoimmune diseases such as Kawasaki disease, systemic sclerosis, and systemic vasculitis (84,125,139). In these studies, sera from patients with and without autoimmune diseases were screened for autoantibodies against different isoforms of Prx.…”
Section: Thioredoxin Target Proteinsmentioning
confidence: 99%
“…Recognition of autoantigens by antiendothelial cell antibodies has been reported [8,9]. We previously demonstrated a marked elevation of a B-cell-activating factor belonging to the TNF family (BAFF) [10] before intravenous immunoglobulin therapy (IVIG), and its steep drop after the therapy [11], which suggest that B-cell activation in the acute phase might be involved in the pathogenesis of KD.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, we have detected more than 150 candidate antigenic spots, and identified more than 50 protein spots. In our earlier study, we identified Peroxiredoxin-2 (Prx2), a member of the Peroxiredoxin (Prx) family of peroxidases, as a target antigen for AECA [9]. In mammalian cells, the Prx family has at least six members (Table 1), and Prx2 is one of the most rapid and potent responders to oxidative stress.…”
mentioning
confidence: 99%
“…To evaluate the roles of AECA in detail, it is essential that their target antigens are identified and that the role of individual target antigens is assessed. Various approaches, such as expression libraries and proteomic, have been developed to identify biomarkers [6][7][8][9][10][11]. In KD, two target antigens for the AECA, tropomyosin and T-plastin, were identified using serological analysis of a recombinant cDNA expression library [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation